2010
DOI: 10.1371/journal.pone.0013579
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Replication-Defective Adenovirus Type 5 HIV Vaccine in Ad5-Seronegative Persons: A Randomized Clinical Trial (HVTN 054)

Abstract: BackgroundIndividuals without prior immunity to a vaccine vector may be more sensitive to reactions following injection, but may also show optimal immune responses to vaccine antigens. To assess safety and maximal tolerated dose of an adenoviral vaccine vector in volunteers without prior immunity, we evaluated a recombinant replication-defective adenovirus type 5 (rAd5) vaccine expressing HIV-1 Gag, Pol, and multiclade Env proteins, VRC-HIVADV014-00-VP, in a randomized, double-blind, dose-escalation, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
(51 reference statements)
6
39
0
Order By: Relevance
“…While the order of vector administration had only minor effects on the magnitude of the IgG response, increasing priming doses of rAd5 led to significantly higher response rates of binding Env-specific IgG after the NYVAC-B boost for consensus A Env gp140 (P = 0.0013), consensus C Env gp140 (P < 0.0001), ConS gp140 (P < 0.0001), A244 gp120 (P = 0.0005), and p24 NYVAC group had 2 participants with erythema and/or induration of greater than 9 cm in diameter after receipt of the fourth vaccination. Overall, the reactogenicity profile was similar to that observed in prior studies of the NYVAC and rAd5 vaccines used in this study (11,12,21).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…While the order of vector administration had only minor effects on the magnitude of the IgG response, increasing priming doses of rAd5 led to significantly higher response rates of binding Env-specific IgG after the NYVAC-B boost for consensus A Env gp140 (P = 0.0013), consensus C Env gp140 (P < 0.0001), ConS gp140 (P < 0.0001), A244 gp120 (P = 0.0005), and p24 NYVAC group had 2 participants with erythema and/or induration of greater than 9 cm in diameter after receipt of the fourth vaccination. Overall, the reactogenicity profile was similar to that observed in prior studies of the NYVAC and rAd5 vaccines used in this study (11,12,21).…”
Section: Resultssupporting
confidence: 82%
“…Both rAd5 and NYVAC-B had previously been tested in humans and have been shown to elicit both humoral and cellular responses (21,25), but the combination of an adenoviral vector with a poxvirus vector had only been tested in NHPs, in which it showed superior protection from acquisition compared with that of homologous poxvirus vectors (20). The rAd5 vaccine used in Interestingly, we found that Env-specific IgA production was mainly restricted to NYVAC/Ad5 hi ( Figure 3D for clade B gp140, P = 0.003 for response rates in NYVAC/Ad5 hi vs. Ad5 hi /NYVAC; Supplemental Figure 4 for clades A and C as well as ConS gp140).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be because of development of immune tolerance at such high doses. Similar results were also observed when only Ad5 based strategy was evaluated in a clinical trial [54].…”
Section: Vaccine Dosesupporting
confidence: 80%
“…Since it has been shown for EBOV and other pathogens, in both nonhuman and human subjects, that heterologous prime-boost vaccination can elicit more potent immunity than single-shot immunization (10,18,39,46) we asked whether rAd26-GP immune responses could be boosted with a heterologous vector to improve protection against EBOV infection. We chose a vaccine dose of 10 11 particles with an eye toward potential clinical testing, as studies have shown this dose of related vectors to be tolerated in human subjects (3,32). Four cynomolgus macaques were inoculated with 10 11 particles (each) of rAd26-GP(Z) and -GP(S/G).…”
Section: Vol 85 2011 Rare Serotype Rad Vector-based Ebov Vaccines 4227mentioning
confidence: 99%